Children and COVID-19 Vaccine: A Public Health Ethics Perspective (Bangladesh Medical Journal, 2022)
As COVID-19 cases were in rise all over the world and the World Health Organization declared a pandemic, there was an increasing focus on availability of new vaccines and drugs against the virus. Meanwhile, we already have several vaccines in COVID-19 vaccination programmes across the globe. During the process of development and clinical trials of the vaccines, several questions were popped up by multiple stakeholders about child vaccination against COVID-19. Most of the queries focused on safety of COVID-19 vaccines, the clinical trial process, priority criteria of getting a vaccine, why and why not children be included in the vaccination programme. In adult population of the country, COVID-19 vaccination programme is being carried out in an unequalled state; the focus is now on paeditric population, as some countries have already started to vaccinate children. At the time of writing this paper when Government of Bangladesh has not yet decided to vaccinate children in the country but initiatives has been taken by health department for above 12 years children vaccination. However, this paper aims to discuss potential ethical dilemmas related to COVID-19 vaccination in children especially in low-resource settings and dig into effective strategies to implement COVID-19 vaccination programme properly in the field of public health.Bangladesh Med J. 2021 Sept; 50(3): 44-48